+0  
 
0
337
4
avatar

I have two equations: 4 = 0.5x*(5-y)^2 and 1 = 0.5x*(3-y)^2 Can you solve this for x and y, and if yes, how?

Guest Apr 4, 2015

Best Answer 

 #4
avatar+80983 
+10

 4 = 0.5x*(5-y)^2 and 1 = 0.5x*(3-y)^2

Rearanging both equations, we have

x = 8/(5- y)^2      and  x = 2/(3-y)^2

This implies that

 8/(5- y)^2  =  2/(3-y)^2      divide both sides by 2

4/(5 - y)^2  = 1/(3-y)^2       cross-multiply  and simplify

4(y^2 - 6y + 9) = y^2 - 10y + 25

4y^2 - 24y + 36  = y^2 - 10y + 25

3y^2 - 14y + 11  = 0    factor

(3y -11) (y - 1) = 0     set each factor to 0

y = 11/3    and y  = 1

And when y = 11/3, x =  9/2        

And when y = 1, x = 1/2

Here's the graph of both    x = 8/(5- y)^2      and  x = 2/(3-y)^2   and the points of intersection

https://www.desmos.com/calculator/ky62ryvrhs

P.S.- The graphs look as though they might intersect below the y axis at some point.....in fact..they don't !!!

 

         

CPhill  Apr 4, 2015
Sort: 

4+0 Answers

 #1
avatar+17711 
+10

You can start by doing this:

4 = 0.5x(5 - y)²  

--->   8  =  x(5 - y)²   --->   8/x  = (5 - y)²   --->   ± √(8)/√(x)  =  5 - y

--->   y  =  5 ± √(8)/√(x)   --->   y  =  5 ± 2√(2)/√(x)

similarly:

1  =  0.5x(3 - y)²

--->   2  =  x(3 - y)²   --->   2/x  = (3 - y)²   --->   ± √(2)/√(x)  =  3 - y

--->   y  =  3 ± √(2)/√(x)

Choosing one from each group and setting them equal to each other:

5 - 2√(2)/√(x)  =  3 - √(2)/√(x)

--->   2  = 2√(2)/√(x) - √(2)/√(x)   --->   2  =  √(2)/√(x)   --->   2√(x)  =  √(2)   --->   √(x)  =  √(2)/2

--->   x  =  2/4   --->   x  =  1/2

When  x  =  1/2, y  =  3 -  √(2)/√(1/2)   --->   y  =  3 - √(4)   --->   y  =  3 - 2  =  1

So, one answer is (0.5, 1).

But, I choose only one possibility from each. Now, it's up to you to choose the other 3 possibilities (not all may work).

This is rather sketchy; if you want further help, please ask.

geno3141  Apr 4, 2015
 #2
avatar
+5

Thank you very much! I tried to isolate x, but that wasn't very helpful, ended up with a long division. 
You're my hero for today! :)

Guest Apr 4, 2015
 #3
avatar+17711 
+5

I'm very glad to be able to help ...

geno3141  Apr 4, 2015
 #4
avatar+80983 
+10
Best Answer

 4 = 0.5x*(5-y)^2 and 1 = 0.5x*(3-y)^2

Rearanging both equations, we have

x = 8/(5- y)^2      and  x = 2/(3-y)^2

This implies that

 8/(5- y)^2  =  2/(3-y)^2      divide both sides by 2

4/(5 - y)^2  = 1/(3-y)^2       cross-multiply  and simplify

4(y^2 - 6y + 9) = y^2 - 10y + 25

4y^2 - 24y + 36  = y^2 - 10y + 25

3y^2 - 14y + 11  = 0    factor

(3y -11) (y - 1) = 0     set each factor to 0

y = 11/3    and y  = 1

And when y = 11/3, x =  9/2        

And when y = 1, x = 1/2

Here's the graph of both    x = 8/(5- y)^2      and  x = 2/(3-y)^2   and the points of intersection

https://www.desmos.com/calculator/ky62ryvrhs

P.S.- The graphs look as though they might intersect below the y axis at some point.....in fact..they don't !!!

 

         

CPhill  Apr 4, 2015

6 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details